PERBANDINGAN HUKUM ANTARA HUKUM BARAT DAN HUKUM ISLAM - Moh. Makmun (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2013)
Abstract : This paper is a study of two laws in society, the Islamic law and the Western law. The study of both is conducted by comparing the terms of the definition, characteristic, objective, and source of law. This study aims to look at the difference of both to find the possibility of co-existing and complement. The main sources of law in Islam are the Qur‟an and Sunnah in addition to the other sources such as ijma‟ (consensus), qiyas(analogical reasoning), istihsan(juridical preference), and maslahah mursalah(unrestricted interest). In addition to Islamic law, the common law, with the characteristics of the prohibition or command that must be obeyed, is also applied in the community. While, the characteristics of Islamic law include: source of Islam, intimately connected and integral to faith and moral of Islam, having two key terms namely the shari‟ah law and jurisprudence, consisting of two main areas namely worship and mu‟amalah in the broad sense, layered structure, consisting of the text of the Qur‟an and the Sunnah. Broadly speaking, the law aims to ensure legal certainty in the community. The law should also consist of justice namely the principles of justice of the community. Due to the dynamic nature of law, the judge as a law enforcement just look codification as a guideline to a legal certainty, whereas in delivering the verdict they must also consider the feeling of justice in society.Kata Kunci: Sumber, tujuan, Hukum Barat, hukum Islam,